Website Landing Page Design For Promotion Of Hartbox Motor Bogor Msme Products - Jihadi, Hilman; Purwandari, Nuraini; Maulana, Dade (Digitus : Journal of Computer Science Applications, 2024)
MSMEs In the era of digitalization and the development of information technology, it is necessary to adopt modern marketing strategies to remain competitive. One effective strategy is to have a good website landing page. This study will explain the design of the landing page of the Hartbox Motor MSME website in Bogor, using a prototype development model. Then the interface and user experience (UI/UX) design process is carried out. The method used is the waterfall method such as requirements, design, implementation, verification and maintenance. This website uses a Use Case Diagram, users are the main actors who can access the entire front page of the website. Then on the Product page, customers can access more details about the Box, Bracket and Accessories. The conclusion of this study is that the results of the analysis of the Hartbox MSME Website needs show several main menus that can be accessed properly which are also depicted in the use case diagram. The design is carried out using Single Page Application Technology, HTML, CSS, JS, which is then hosted on the server, making it easier for buyers to see all the needs on the Hartbox MSME Website.